Proceedings of 3rd IEEE International Symposium on High Performance Distributed Computing
DOI: 10.1109/hpdc.1994.340265
|View full text |Cite
|
Sign up to set email alerts
|

The virtual computing environment

Abstract: A network of supercomputers and high-performance workstations appears to be the only reasonable way to provide adequate computing resources for the Grand Challenge problems of the next century. Such a collection of computers and supporting software environments is called a virtual computing environment (VCE). This paper describes the motivation and goals of the VCE project, followed by a description of the system. The paper concentrates on the runtime aspects of the VCE, and concludes with a discussion of a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…There are other metasystems [17][30] [43][50] and heterogeneous parallel computing [7][10] [18][46] projects underway. Our work differs from other heterogeneous parallel processing systems in the scope.…”
Section: Related Workmentioning
confidence: 99%
“…There are other metasystems [17][30] [43][50] and heterogeneous parallel computing [7][10] [18][46] projects underway. Our work differs from other heterogeneous parallel processing systems in the scope.…”
Section: Related Workmentioning
confidence: 99%
“…Building these memories bv hand can be an enormouslv difficult knowledge engineering task. ~e c e n t work has shown that large case bases can be automatically generated with A1 techniques (3) and accessed extremely efficiently by parallel inferencing techniques (4). 2) Hybnd knowledge and databases.…”
mentioning
confidence: 99%